Behavioural predictors of subsequent hepatitis C diagnosis in a UK clinic sample of HIV positive men who have sex with men. Issue 4 (28th July 2006) - Turner, J M; Rider, A T; Imrie, J; Copas, A J; Edwards, S G; Dodds, J P; Stephenson, J M
Abstract : Objective: To explore the associations between self reported high risk sexual behaviours and subsequent diagnosis with hepatitis C virus (HCV) infection. Methods: The Sex, Health and Anti-Retrovirals Project (SHARP) was a cross sectional study of sexual behaviour in HIV positive, men who have sex with men (MSM) attending a London outpatient clinic. From July 1999 to August 2000 participants completed a computer assisted self interview questionnaire (CASI) on recent sexual behaviour, recreational drug use, and detailed reporting of the last two sexual episodes involving different partners. Results were combined with routine clinic data and subsequent testing for HCV up to 21 April 2005. A new HCV diagnosis was defined as anti-HCV antibody seroconversion or positive HCV RNA following a previous negative. Incident rate ratios (IRR) were calculated using Poisson regression in Stata (version 9). Men contributed time at risk from interview until either their diagnosis or their last negative test result. Results: Of the 422 men who completed questionnaires, 308 (73%) had sufficient clinical and HCV testing data available for analysis. Incident HCV infection was identified in 11 men. Unprotected anal intercourse, more than 30 sex partners in the past year, higher numbers of new anal sex partners, rimming (oro-anal sex), fisting, use of sex toys, and intranasal recreational drug use were associated with HCV. In multivariate analysis only fisting remained associated with HCV (adjusted IRR 6.27, p = 0.005). Conclusions: In this study of HIV positive MSM, fisting is strongly associated with HCV infection. Where individuals report high risk sexual behaviours, clinicians should offer appropriate testing for HCV infection.